Kisspeptin as a therapeutic target in reproduction. (3rd May 2016) - Yang, Lisa; Dhillo, Waljit
ABSTRACT: Introduction : Kisspeptins are a family of neuropeptides whose identification has become one of the biggest discoveries in reproductive endocrinology during the past decade. Kisspeptins act upstream of GnRH as high-level mediators of the reproductive axis. Areas covered : The authors performed a search of all publications on kisspeptin since its discovery in 1996. A full appraisal of the expanding literature concerning kisspeptin is beyond the scope of this review. This article therefore aims to cover the principle human studies outlining kisspeptin action in human physiology and to discuss the key findings, describing kisspeptin's potential as a therapeutic target in human reproduction. Expert opinion : The identification of the kisspeptin signaling pathway has greatly advanced the study of reproductive endocrinology. Building on a large body of animal data, a growing number of human studies have shown that exogenous kisspeptin can stimulate physiological gonadotropin responses in both healthy subjects and those with disorders of reproduction. There is an increasing appreciation that kisspeptin may act as a signal transmitter between metabolic status and reproductive function. Future work is likely to involve investigation of novel kisspeptin analogs and further exploration of role of neurokinin B and dynorphin on the kisspeptin-GnRH axis.